Phagocytosed Bordetella pertussis Fails To Survive in Human Neutrophils - Lenz, Derrick H. (American Society for Microbiology, 2000)
Previous studies have reported that phagocytosed Bordetella pertussis survives in human neutrophils. This issue has been reexamined. Opsonized or unopsonized bacteria expressing green fluorescent protein (GFP) were incubated with adherent human neutrophils. Phagocytosis was quantified by fluorescence microscopy, and the viability of phagocytosed bacteria was determined by colony counts following treatment with polymyxin B to kill extracellular bacteria. Only 1 to 2% of the phagocytosed bacteria remained viable. Opsonization with heat-inactivated immune serum reduced the amount of attachment and phagocytosis of the bacteria but did not alter survival rates. In contrast to previous reports, these data suggest that phagocytosed B. pertussis bacteria are killed by human neutrophils.